Education in the Age of AI: From Digital Teachers to Artificial Intelligence-Based Learning - Kristia Fatmasari, Ria (Journal of English Language and Education, 2026)
This study aims to comprehensively analyze how AI integration changes the role of educators, learning models, and the dynamics of the teaching and learning process at various levels of education. The research method used is a descriptive-qualitative approach with data collection techniques through literature studies, limited observations, and in-depth interviews with teachers, students, and educational technology experts. The results show that AI is able to provide personalized learning, more efficient classroom management, automated assessment systems, and self-learning support through smart chatbots and digital tutors. This study concludes that education in the AI era demands a repositioning of the role of teachers from conventional teachers to facilitators of technology-based learning, while ensuring that the use of AI remains ethical, inclusive, and oriented towards the development of students' character. These findings provide implications for policymakers, educational institutions, and technology developers to design an adaptive, humanistic, and sustainable education ecosystem amid the accelerating development of AI.